A tephra‐based correlation of marine and terrestrial records of MIS 11c from Britain and the North Atlantic. (8th September 2021) - Candy, Ian; Tye, Gareth; Coxon, Peter; Hardiman, Mark; Matthews, Ian; Palmer, Adrian
ABSTRACT: Resolving marine and terrestrial records of glacial and interglacial stages has long been a challenge for Quaternary studies. We present a tephra‐based correlation for MIS 11c of a North Atlantic marine core and a British terrestrial record (Marks Tey). A varved chronology is presented for the annually laminated lake sequence at Marks Tey and the proxy data from this site are plotted on an annual timescale for the first time. This record shows clear evidence for an abrupt cold event and corresponding ecological and landscape response. Varve counting shows that the abrupt event lasted for ca 185 a but the impact on the landscape persisted for ca 560 a. The co‐occurrence of a single tephra layer in Marks Tey and ODP 980 allows these two records to be correlated. Furthermore, this synchronisation shows that the abrupt cold event in Marks Tey was coincident with a centennial‐scale cold event in ODP 980, as evidenced by an increase in Neogloboquadrina pachyderma (s) percentage. In both ODP 980 and Marks Tey the age of this abrupt event was ca 414 500 a indicating that, at this point in MIS 11c, a widespread cold event occurred in the northeastern Atlantic and the British Isles.